The Easterlin threshold: a first glimpse - STRATI, Francesco (Journal of Mathematical Economics and Finance, 2015)
This work is supposed to introduce and set up a theoretical model which depicts the time dy- namics of the relations between income and happiness. By using two distortions: the materialism and the run e_ect, the model conceives a happiness-income ratio as dependent on the locus of the graph in which they are placed. Their positive or negative relations depend on the level of income: for a level beyond the Easterlin threshold the happiness decreases, for a low level of income happiness increases, while in the midst of these loci the level of happiness increases in average but marginally decreases as income increases.